Learning the birds a midlife adventure - Rogers, Susan Fox (Three Hills, an imprint of Cornell University Press, 2022)
"A midlife birding memoir that travels from New York State to Alaska as the author ventures out in pursuit of birds. History and natural history combine as the author comes to know the birds"--